FORMALDEHYDE ADSORPTION IN AQUEOUS SOLUTION USING EGGSHELL TREATED WITH PLASMA TECHNOLOGY - Chainetr, Siraprapa; Khiewwijit, Rungnapha; Dechthummarong, Chanchai; Ngoenkhumkhong, Khanchit (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The aim of this study was to compare the adsorption potential of formaldehyde in aqueous solution using treated eggshell with plasma technology to untreated eggshell, based on factors affecting adsorption such as initial concentration of aqueous formaldehyde (10-50 mg/L), contact time (5-360 minutes), and Sieve no.12, 16 and 20 eggshell sizes in which referred to the particle size diameter of eggshell of ≤ 1.70 mm, ≤ 1.18 mm and ≤ 0.85 mm, respectively. All tests were performed in a laboratory scale. Moreover, the isotherm of formaldehyde adsorption was also examined. The results showed that plasma treatment of eggshell could efficiently increase the adsorption potential of formaldehyde. The optimal conditions for formaldehyde adsorption using eggshell treated with plasma technology were a 30 mg/L initial concentration of aqueous formaldehyde, a contact time of 120 minutes, and Sieve no.16 eggshell size. The average formaldehyde adsorption efficiency was 90.53±0.00% under this optimal condition, compared to 56.17±2.34% when using untreated eggshell. Additionally, the results showed that adsorption isotherm was more fitted by Langmuir than Freundlich. The maximum adsorption capacity of eggshell treated with plasma was 18.203 mg/g, which was 3.8 times higher than the capacity of untreated eggshell. This study provided a development of efficient adsorption of formaldehyde by using advanced technology for modifying absorbent in which focused on the use of wastes, such as eggshell. Furthermore, results obtained in this study can be used to further develop the treatment of formaldehyde industrial wastewater in the future.